PENGARUH DISIPLIN KERJA, KOMUNIKASI DAN STRES KERJA TERHADAP KEPUASAN KERJA PADA PT. SARANA AGRO NUSANTARA - Midayanti Siahaan; Yuli Arnida Pohan (Jurnal Widya, 2024)
This research aims to determine the influence of communication work discipline and work stress on job satisfaction at PT. Sarana Agro Nusantara. This research used a total of 70 respondents. The data collection techniques used in this research used questionnaires and interviews. The testing techniques used in this research are research instrument tests, descriptive statistical tests, classical assumption tests, multiple linear regression tests and hypothesis tests. The results obtained from hypothesis testing are that the work discipline variable has no positive and significant effect on employee satisfaction, then the communication variable has a positive and significant effect on employee satisfaction and the work stress variable has a positive and significant effect on employee satisfaction at PT. Sarana Agro Nusantara. Simultaneously, the results showed that the variables of work discipline, communication and work stress had an effect on employee satisfaction at PT. Sarana Agro Nusantara.